An unusual case of cardiac tamponade: Bronchogenic cyst infection due to Salmonella bredeney. Issue 2 (February 2019) - Yildiz, Halil; Reichwein, Ruth; Poncelet, Alain; Lacroix, Valerie; D'abadie, Philippe; Ghaye, Benoit; Hoton, Delphine; Yombi, Jean Cyr
Abstract: We present an unusual case of cardiac tamponade in a 17-year-old girl immunocompetent patient due to Salmonella enterica ssp. bredeney following infection of a bronchogenic cyst. The patient was admitted to hospital with pleuritic chest pain, dyspnoea and fever. Pulmonary angio-CT showed a bronchogenic cyst compressing the left atrium. The echocardiography showed diffuse pericardial effusion with right ventricular collapse consistent with cardiac tamponade. Pericardiocentesis was performed and microbiological cultures of the pericardial fluid became positive for Salmonella species confirmed later as bredeney subspecies by PCR . Empirical antibiotherapy was started with intravenous (IV) ceftriaxone. Bronchogenic cyst infection was suspected and confirmed by 18 FDG PET CT. The patient was successfully treated by complete resection of the cyst and continuation of IV ceftriaxone followed by oral amoxicillin/clavulanate for a total duration of 6 weeks. She then completely recovered and didn't present any relapse after 6 months of follow up.